ECOTOURISM, SOCIAL INEQUALITY, AND PERCEPTUAL GAPS:: A STUDY OF CONSERVATION AND LOCAL ECONOMIC DEVELOPMENT AT DLUNDUNG WATERFALL - Diyni, Alfa Maziyyata; Maulidah, Fadiah Hanim; Al Bustomi, Budairil Munir; Pratama, Handika; Dila, Yasmin Fara; Afifah, Silvi Nur (The Indonesian Journal of Social Studies, 2026)
This study aims to analyze the influence of ecotourism potential at Dlundung Waterfall on nature conservation and local economic development in Ketapanrame Village, Trawas, Mojokerto. A quantitative associative approach was employed using quota sampling, involving 60 local residents and 40 tourists. Data were collected through questionnaires and analyzed using simple linear regression, t-test, F-test, and coefficient of determination. The results indicate that ecotourism potential has a significant positive effect on nature conservation according to both residents (R² = 0.333; F = 18.971) and tourists (R² = 0.358; F = 32.336). However, ecotourism potential does not significantly affect local economic development based on residents’ perception (R² = 0.040; F = 1.571), while tourists perceive a significant but weak relationship (R² = 0.067; F = 4.198). These findings reveal a statistically confirmed perceptual gap (Fisher’s z = −2.21, p = .027) indicating unequal distribution of economic benefits. This study concludes that ecotourism success should be measured not only by environmental outcomes but also by equitable economic benefits for local communities. Practically, these findings suggest that the management of Dlundung Waterfall ecotourism needs to shift toward a more participatory model: Perum Perhutani and the Ketapanrame Village Government should establish a formal community co-management mechanism that expands residents’ roles beyond labor into profit-sharing, business licensing, and joint decision-making, so that the economic gains already visible to tourists are also meaningfully experienced by the local community.